Verimlilik ölçümünde hedef programlama ve bir uygulama - Derman, Neslihan (Fen Bilimleri Enstitüsü, 1994)
Bir ülkenin kalkınması, ister sanayide, isterse tarım ve hizmet sektöründe olsun, sahip olduğu kaynakları verimli kullanarak ekonomik gelişme kaydetmesine bağlıdır. Günümüzde, aynı anda birden fazla çelişen amacı tatmin ederek optimal çözümler bulma zorunluluğu, çok amaçlı programlama tekniklerini ortaya çıkarmıştır. Bu tekniklerden biri olan Hedef Programlama genel yapısı itibariyle saptanan hedeflerden sapmaları minimize etmeye çalışır. Bu çalışmada, verimlilik ve hedef programlama açıklamaları yapıldıktan sonra, bir uygulama ile oluşturulan bir hedef programlama modeli üzerinde verimlilik analizleri yapılmıştır. İkinci bölümde, verimlilik kavramı, verimliliği etkileyen faktörler ve verimlilik ölçme yöntemleri anlatılmıştır. Üçüncü bölümde, hedef programlamanın uygulama alanları, verimlilik Ölçümünde hedef programlamaya değinilmiştir. Dördüncü bölümde ise, Bekoteknik A.Ş. 'de yapılan bir uygulama ile önce bir hedef programlama modeli oluşturulmuş, daha sonra da elde edilen üç değişik üretim planına uygun olarak verimlilik analizleri yapılmıştır.

The importance of productivity and its measurement has been well recognised. The concept of Productivity is still vaguely defined and least understood, although it is probably the most widely discussed topic. Productivity is concerned with the effective and efficient utilization of resources (inputs) in producing goods and/ or services (outputs). The terms productivity, efficiency and effectiveness are confused with each other. Efficiency is the ratio of actual output attained to standart output expected. Effectiveness is the degree of accomplishment of objectives. Productivity is a combination of both effectiveness and efficiency, since effectiveness is related to the performance while efficiency is related to resource utilization. Efficiency and effectiveness need not to together, because efficiency implies reaching a certain level or range of results that is acceptable but not necessarily desirable. The relationship between productivity, effectiveness and efficiency is given below = r»,.~-j"~*.,-,,,. *.,.",- output Performance- achieved _ effect! vetıes s Produc tıvı tiy- - : - - - = ? -3 -^^-. - ;?? input resourcesconsumed efficiency Productivity is a major concern for any organization because it determines the well-being of the organization and its members. Productivity is also one the most important issues at the national level. The level of uproductivity, or the success of management, depends on the execution of certain -viii- managerial functions like planning, organizing, directing and controlling. If we closely examine various definitions and interpretations of productivity, three basic types of productivity appear. Partial productivity is the ratio of output to one class of input. For example, labor productivity (the ratio of output to labor- input) is a partial productivity measure. Total factor productivity is the ratio of net output to the sum of associated labor and capital (factor) inputs. Total productivity is the ratio of total output to the sum of all input factors. In this study, a model to measure productivity of an organisational system is presented. Productivity has been viewed in a broader perspective to represent the degree of accomplishment of performance objectives, reconciled optimally through Goal Programming. The measurement is even more clouded with confusion as it is only a process of translating the concept and objectives into a methodology. This study attempts to examine productivity in its broader perspective as an index of the accomplishment of the goals of an organisation viewed as a system. A detailed methodology is developed so as to take into account the relevant goals and the total inputs needed. A productivity index cannot be viewed as an abstract number; it should convey a meaning and a message. Measurement of productivity can therefore, be recommended to concern with the following objectives: - to help idetify potential for improvement. - to help locate areas for re-allocation and deployment of resources. - to help provide measures which become representative of the accomplishment of the defined and the established goalsin the hands of the user -IX- In brief, the measurement of productivity should be viewed as an exercise to obtain more effective performance of the organisation» Productivity is a complex issue governed by multiple goals, some of which are in conflict/] It is affected by the outcome of the different productive sectors in the society; their driving factors and the interactions among those factors on the hand, and among the different sectors on the other hand. Goal Programming is an appropriate technique for group studies._J The research studies show that goal programming has been applied in many different sciences and that tremendous potential remains for further expansion and application of this technique. The general" model for goal programming is described as ; Minimi seZ^Yj £ pj ( wij> di+^ij ? di> Subject - ]T Aijxj+d~-dJ=bi{.i^lr2t...,m) 3=A Xj.di.dito Where Pj is the pre-emptive priority and j is the rank of each goal. The variable Xj represents a decision variable. VI ^ and W^ represent the weights given each goal, and d^ and d^ represent the degree of under or over - achievement of a goal, respectively. hL^ is the technological coefficient while b^ is the goal level. The major objectives are usually to meet the organisation's goals of increasing productivity, quality, employee participation and job satisfaction, as suggested by the following factors. -x- (a) Maximise utilisation of manpower. (b) Minimise cost. (c) Increase worker participation. (d) Minimise the cost saving ratio. (e) Improve quality. (f) Increase productivity. Since identifying goals and their prioritiesis management's responsibility, these goals and their related pre-emptive priorities could be changed and some goals added or eliminated. In the second chapter, besides the definition of productivity and the concepts which has relationship with productivity, it is touched to the productivity subjects on the level of economy, management and individual"} This chapter contains also measurement of productivity. In this chapter, productivity measurement methods as ; - International productivity measurement - National productivity measurement - Industrial productivity measurement - Productivity measurement of an organisation. has been told briefly. The classification of the literature models for the measurement of productivity and the problems faced in productivity measurement models are also dealt with in the same chapter. The third chapter contains productivity measurement through goal programming. In this chapter, the formulation of goal programming, the working areas of goal programming and the relationship between the productivity measurement and the goal programming is explained. The fourth chapter is a case study which shows a productivity measurement through goal programming in an electronical organisation. First of all, the actual data performance of the organisation has been determined. Then, the policy norms of BEKO has been described by three sub-systems (Production Sub-system, Marketing Sub-system and Material Sub-system). Through these sub-systems, the goal- programming formulation has been determined. For the goal-programming formulation; -xi- - capacity determination, - profit determination, - sales determination, - energy and system determination, - demand determination, has been used. The result of the goal-programming has been given three different product plans. These plans have been examined by productivity measurement to choose one (the best) of them. By these product plans, the items which are important for the organisation have been choosed. Then, the sub-sy stems and the key performance areas have been determined. After than, the weightage factors of the actual and objectivated values have been calculated. Through the weightage factors, productivity measurement of each system and sub-system have been calculated. At the end, the highest productivity indice of the product plan has been choosed. An important contribution of the process of productivity measurement through this model is that it sets out realisable targets and goals, as objectivated output.
Goal programming in productivity measurement an application
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Hedef programlama; Verimlilik ölçümü; Goal programming; Productivity measurement